The concept of the social in uniting the humanities and social sciences - Brown, Michael E. 1938- (Temple Univ. Press, 2014)
"In this book, Michael Brown provides original and critical analysis of the state of the social sciences and the humanities. He examines the different disciplines that address human affairs--from sociology, philosophy, political science, and anthropology to the humanities in general--to understand their common ground. He probes the ways in which we investigate the meaning of individuality in a society for which individuals are not the agents of the activities in which they participate, and he develops a critical method for studying the relations among activities, objects, and situations. The Concept of the Social in Uniting the Humanities and Social Sciences restores the centrality of sociality to all disciplines that provide for and depend on the social dimension of human life. Ultimately, he establishes a theory of the unity of the human sciences that will surely make readers rethink the current state and future of theory in those fields for years to come. "--